The improvements needed for environmental information in Japan. - Abe, Naoya (Asean Engineering Journal)
Environmental information is vital for effective and sound decision-making process. However the collection of environmental information and its conversion into a usable form is not free of charge and often requires some time to become available, since various types of information need to be integrated due to the fundamental interdisciplinary nature of the environment and our society. Ultimately, environmental information is meaningless if it is not used; the collection and generation of environmental information should not be merely a goal; rather, it is the means for better decision-making. Japan has developed and advanced an environmental information system and has probably entered into the next stage where we need to re-align and re-design the manner of collecting, managing and using the information under various constraints (especially financial constraints).